2012
DOI: 10.5005/jp-journals-10013-1130
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon and Atypical Sinonasal Masses: Diagnostic and Therapeutic Challenges

Abstract: Introduction: Sinonasal masses are a wide range of pathologies ranging from simple nasal polyps to rare tumors like esthesioneuroblastomas. Early symptoms of all of them are similar to common nasal and sinus problems, hence, producing a delay in diagnosis. . Detailed history and ENT examination were recorded. Radiological investigation was carried out in the form of computed tomographic (CT) scan of nose and paranasal sinuses. Final diagnosis was made by histopathological examination either before instituting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…18 Incidence of mucocele (1 case-2.44%) in our study matched that of Wahid FI et al 19 (2.22%). Sharma R et al 7 reported a higher incidence (7%) in their study of 223 cases.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…18 Incidence of mucocele (1 case-2.44%) in our study matched that of Wahid FI et al 19 (2.22%). Sharma R et al 7 reported a higher incidence (7%) in their study of 223 cases.…”
Section: Discussionmentioning
confidence: 83%
“…5 It was the second most common non-epithelial benign neoplasm (16.67%) in the present series. Modh SK et al 6 and Sharma R et al 7 reported an incidence of 19.4% and 11% respectively in their studies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…These results emphasize the overall malignant transformation potential to about 1-2% [12]. However, the incidence of oral and upper respiratory tract SCC is on the rise with a high level of recurrence [13,14,15,16]. This necessitates a better understanding of the neoplastic transformation at cellular level.…”
Section: Introductionmentioning
confidence: 91%
“…The majority of sinonasal pathology is inflammatory and neoplasms comprising of 3% of head and neck tumors. 6 Almost all sinonasal masses present with varying symptoms of nasal obstruction, epistaxsis, nasal discharge, loss of smell or change in perception of smell, oral symptoms, facial swelling, orbital symptoms and ear symptoms. 7 A detailed history, clinical examination, diagnostic nasal endoscopy and advanced imaging (CT scan) are required to make a presumptive diagnosis.…”
mentioning
confidence: 99%